Braided Stories and Bricolaged Symbols: Critical reflection and transformative learning theory for teachers - Brigham, Susan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
In this paper I make the case that transformative learning theory, a specific adult learning theory, and an arts-informed research method have important value for teacher professional practice and teacher education. I refer to two phases of a study involving women who have immigrated to Maritime Canada and were teachers in their countries of origin. I illustrate a process through which participants can weave multiple perspectives, unpack constructed realities, and become more reflective about their teacher identity and teaching practice.